Burden of hospitalizations in newly diagnosed heart failure patients in Poland: real world population based study in years 2013–2019 - Przemysław Leszek; Daniel Waś; Kinga Bartolik; Kladiusz Witczak; Andrzej Kleinork; Bohdan Maruszewski; Katarzyna Brukało; Paulina Rolska‐Wójcik; Małgorzata Celińska‐Spodar; Tomasz Hryniewiecki; Marta Załęska‐Kocięcka (ESC Heart Failure)
Abstract Aims We aim to report trends in unplanned hospitalizations among newly diagnosed heart failure patients with regard to hospitalizations types and their impact on outcomes. Methods and results A nation‐wide study of all citizens in Poland with newly diagnosed heart failure based on ICD‐10 coding who were beneficiaries of either public primary, secondary, or hospital care between 2013 and 2018 in Poland. Between 1 January 2013 and 31 December 2019, there were 1 124 118 newly diagnosed heart failure patients in Poland in both out‐ and inpatient settings. The median observation time was 946 days. As many as 49% experienced at least one acute heart failure hospitalization. Once hospitalized, 44.6% patients experienced at least one all‐cause rehospitalization and 26% another heart failure rehospitalization. The latter had the highest Charlson co‐morbidity index (1.36). The 30 day heart failure readmission rate was 2.96%. Kaplan–Meier analysis revealed very early readmissions (up to 1–7 days) were associated with better survival compared with rehospitalization between 8 and 30 days. All‐cause mortality was related to the number of hospitalization with adjusted estimated hazard ratios: 1.550 (95% CI: 1.52–158) for the second HF hospitalization, 2.158 (95% CI: 2.098–2.219) for third, and 2.788 (95% CI: 2.67–2.91) for the fourth HF hospitalization and subsequent ones, as compared with the first hospitalization. Conclusions Among newly diagnosed heart failure patients in Poland between 2013 and 2019, nearly half required at least one unplanned heart failure hospitalization. The risk of death was growing with every other hospital reoccurrence due to heart failure.